MENINGKATKAN HASIL BELAJAR SISWA MELALU MODEL KOOPERATIF BAMBO DANCING PADA MATERI SUMBER ENERGI ALTERNATIF - Bahansubu, Sherina; Anwar, Herson; Hiola, Zohrawaty (DIRASATUL IBTIDAIYAH, 2024)
AbstractThe formulation of the problem in this research is "Can the Bambo Dancing Cooperative learning model improve the cognitive learning outcomes of class IV students at SD Muhammadiyah 2 Limboto". This type of research is Classroom Action Research (PTK). The subjects of this research were 20 grade IV students at SD Muhammadiyah 2 Limboto. Data collection techniques use observation and documentation. The success indicator is marked as a minimum of 90% of the number of students who achieve the KKM score. Based on the research results, it shows that the application of the Bambo Dancing learning model to fourth grade students at SD Muhammadiyah 2 Limboto can improve student learning outcomes in science learning alternative energy sources. Student learning outcomes increased after taking action in cycle I by 60%. Student learning outcomes increased again in cycle II to 85% which had reached the KKM. This means that in cycle II students increased by 25%. Thus, it can be concluded that using the Bambo Dancing learning model can increase student learning activities in science learning in class IV at SD Muhammadiyah 2 Limboto.Keywords: Learning Outcomes, Cooperative Bambo Dancing Model, Science Learning AbstrakRumusan masalah pada penelitian ini adalah “Apakah model pembelajaran Kooperatif Bambo Dancing dapat meningkatkan hasil belajar kognitif siswa kelas IV SD Muhammadiyah 2 Limboto”. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK). Subjek penelitian ini adalah siswa kelas IV SD Muhammadiyah 2 Limboto yang berjumlah 20 siswa. Teknik pengumpulan data menggunakan observasi dan dokumentasi. Adapun indikator keberhasilan ditandai minimal 90% dari jumlah siswa yang mencapai nilai KKM. Berdasarkan hasil penelitian menunjukkan bahwa penerapan model pembelajaran Bambo Dancing pada siswa kelas IV SD Muhammadiyah 2 Limboto dapat meningkat hasil belajar siswa pada pembelajaran IPA sumber energi alternatif. Hasil belajar siswa mengalami peningkatan setelah dilakukan tindakan pada siklus I sebesar 60%. Hasil belajar siswa mengalami peningkatan kembali pada siklus II menjadi 85% yang telah mecapai KKM. Artinya, pada siklus II siswa meningkat sebesar 25%. Dengan demikian dapat disimpulkan bahwa menggunakan model pembelajaran Bambo Dancing dapat meningkatkan aktivitas belajar siswa pada pembelajaran IPAdi kelas IV SD Muhammadiyah 2 Limboto. Kata Kunci: Hasil Belajar, Model Kooperatif Bambo Dancing, Pembelajaran IPA